2015
DOI: 10.1016/j.phpro.2015.08.083
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Chirp-coded Excitation Method in Order to Improve Geometrical and Acoustical Measurements in Wood Specimen

Abstract: International audienceMethods for measuring ultrasonic wave velocity in an elastic material require knowledge of the thickness of the sample. In general, the precision of this knowledge determines the accuracy of the experimental technique for measuring velocity. With the same restriction, measuring thickness of a material require a knowledge of the time-of-flight of the wave propagating. This problem is particularly acute in measuring parameters in wood specimen with an acoustical impedance contrast higher th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…When a recognizable signature is sent through the media, such as chirp signal, input and output signals delay time can be obtained using cross-correlation [26,27,28]. The maximum value for the crosscorrelation function between two signals indicates their delay time.…”
Section: Cross-correlationmentioning
confidence: 99%
See 1 more Smart Citation
“…When a recognizable signature is sent through the media, such as chirp signal, input and output signals delay time can be obtained using cross-correlation [26,27,28]. The maximum value for the crosscorrelation function between two signals indicates their delay time.…”
Section: Cross-correlationmentioning
confidence: 99%
“…Automatic methods for detecting first arrivals have been proposed, including pickers based on the Akaike information criteria (AIC) [23,24] and the Hinkley criteria [25]. Alternatives include the transmission of encoded waveforms, such as the chirp-coded excitation method, where a recognizable signature is sent through the media and the TOF is estimated using a cross-correlation function [26,27,28]. In consideration of the wide range of signals and TOF detection techniques, the choice of pa-…”
mentioning
confidence: 99%
“…Depending on the wavelength, this causes an overlap between the wave packets that results in a significant loss of information. Lasaygues et al [11] showed that the duration of the chirp signal had a weak influence on the calculation of physical parameters such as the thickness and the ultrasonic wave velocity.…”
Section: Introductionmentioning
confidence: 99%